Rotinas nos processos de ensino e de aprendizagem nos anos iniciais do ensino fundamental - Iijima, Danieli Winck (2014)
Considering school as an institution responsible for ensuring new generations to acquisition of knowledge historically constructed by mankind was sought, with this research to understand the routines in the teaching and learning processes in the early years of elementary school. We understand routine as those daily, repetitive and regular activities that occur in a particular quotidian, seeking organize it. Was held, in addition to a literature search, which sought to embrace the main authors who discuss this subject: Barbosa (2000), Cavasin (2008), Rodrigues (2009) and Lima (2010), an ethnographic study spanning two municipal schools in the region of Cascavel city. The fieldwork, whose data were collected through observation, using the cursive register technique, aimed to describe the pedagogical activities in the early years of elementary school, focusing on routines. In Phase I, it was observed for three days, the first and second year of elementary of two schools, totaling 48 hours. So it was decided, in phase II, concentrating the 48 hours of observation in a single class. Found a predominance of routines totaling between 52 and 72 percent of other educational activities in school life. Based on observations, the routines were classified as related to the organization of time, space, compliance with school rules and structuring of content. Considering the high frequency of the routines in the pedagogical process, emphasizes the importance of giving them the same treatment given to other activities developed by the teacher, planning them intentionally. Dialogues in the sense that, by targeting the formative aspect in education, routines can be constituted both an educational category that contributes to students learn the scientific knowledge, which process, school is responsible; as unlike can characterize an activity that hinders the learning process, making it uninteresting and boring, if not planned and diversified.